A device to measure wheel slip to improve the fuel efficiency of off road vehicles. (April 2017) - Ashok Kumar, A.; Tewari, V.K.; Gupta, Chanchal; Pareek, C.M.
Highlights: A hall sensor based wheel slip measurement system is developed. An embedded digital indicator was developed to control wheel slip. Evaluated under laboratory as well as in the field condition. The developed device is simple in construction. Can be fitted to any make and model of tractor. Abstract: A hall sensor based simple technique was introduced to measure wheel slip and a microcontroller based embedded digital system was developed to display wheel slip data and warn the operator with audible and visible warnings if the optimum range is exceeds. Hall sensor slip measurement system was validated in controlled soil bin condition, tar macadam surface and actual field condition and compared with the commercial radar sensor. The developed system is simple in construction and can be mounted to any make and model of agricultural tractors by entering the appropriate rolling radius via the computer interface. Field trials were conducted to measure wheel slip and fuel consumption on farm use with and without activation of slip indicator; it was observed that, the amount of fuel saving during various agricultural operation was up 1.3 l/h.